PERKEMBANGAN PENSEJARAHAN ISLAM DI ALAM MELAYU (Development of Islamic Historiography in Malay Archipelago) - Mohd Noor, Arba’iyah (Journal of Al-Tamaddun, 2011)
This article seeks to introduce the development of Islamic historiography in the Malay Archipelago. The chronology of the development of Islamic historiography starts off with the spread of Islam in this region in the seventh century. The greatest accomplishment however, was the role of the Quran and some Islamic historiographies that provided some historical inspirations and consciousness to the Malays in their understanding of Islamic history.